Pengaruh Model Pembelajaran Scramble Berbantuan Media Peta Terhadap Minat Belajar IPS Siswa Kelas IV - Ramadania, Ajeng Nurastuti; Idris, Muhammad; Ramadhani, Efran (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Pahlawan Tuanku Tambusai, 2022)
This research was motivated by the low interest in learning IPS students of class IV. The purposeof this study is to find out the influence of the map media-assisted scramble learning model on thelearning interests of fourth grade students. The study used experimental quantitative methods and one-group-pretest-posttes design research types. Sampling using random sampling methods. Data collection techniques in this study used the Guttman scale in the form of questionnaires, interviews and documentation. The average on pretest results 17 with a percentage of 61% belongs to the